Pengembangan Strategi Pemasaran Terhadap Usaha Bengkel Las - Acep Hidayat; Muhammad Ja’farullah Zain; Dwi Epty Hidayaty (Yayasan Daarul Huda Kruengmane, 2023)
The motivation behind this article is to act as an aide to the whole community, especially the youth who have a passion for building welding workshops. This talk explains the right way to build a welding studio business in an organized way through the usual stages. Running a welding studio for the production of gratings, siding, overhangs, stairs and so on. is very exhilarating and can bring in significant salary and profit, assuming it is done diligently and with passion, and with genuine concern for the wishes of the client. Customers or the general public usually follow trends or time, so they often want to make the latest designs for home displays. So that the planned business can be carried out systematically, we can prepare all stages.